Adaptacija vostocnoaziatskoj psichotelesnoj teorii licnosti k ocestvennoj sisteme sportivnych edinoborstv - Voronov, I. A. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The psychosomatic theory of a person practically used in such spheres of activity, as spiritual development, improving gymnastics and single combat has existed for some millennia in East Asia.